OPTICAL PROPERTIES OF REDUCED GRAPHENE OXIDE ON IRON OXIDE NANOPARTICLES - Bala, D. A.; Ali, H.; Eli, D.; Yunana, T. (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, we have successfully synthesized iron oxide/reduced graphene oxide (Fe3O4/rGO) nanocomposite materials using a simple, friendly, cost-effective and non-toxic chemical method at room temperature. From the results, the absorbance spectrum of Fe3O4/rGO has demonstrated a redshift to higher wavelength when compared to Fe3O4 spectrum. This indicates an increase in visible light absorption which could be attributed to the formation of chemical bond between Fe3O4 nanoparticles and rGO. The results offer a possible method to dramatically enhance the optical absorption and photocatalytic activity of materials by employing rGO nanostructures and also provide further insight into the development of ideal functionality for future optoelectronic systems.
Keywords: Fe3O4 nanoparticles, graphene, photocatalytic, nanocomposite